(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Determine the rate of urinary tract fungal infections in patients being treated at Tra Vinh General Hospital and determine some factors related to the rate of urinary tract fungal infection in patients. Method: Patients being treated as inpatients at Tra Vinh General Hospital with symptoms of urinary tract infection. Descriptive cross-sectional study from 27/5/2024 to 4/8/2024. Results: The group of patients aged 60 years and older accounted for more than half of the studied sample (55.7%), the oldest age was 90 years old and the youngest was 23 years old, the average age was 60.12 ± 14.43. Of which, women accounted for 61.4% and Kinh people made up the majority at 70.2%. Renal failure accounted for 10.1%, diabetes mellitus accounted for the highest rate of associated diseases surveyed at 22.1%. Conclusion: In a total of 158 subjects participating in the study, when cultured in Sabouraud agar, the rate of urinary tract fungal infection was 16.5%.